Reviewing Perovskite Oxide-Based Materials for the Effective Treatment of Antibiotic-Polluted Environments: Challenges, Trends, and New Insights - Afonso Henrique da Silva Júnior; Carlos Rafael Silva de Oliveira; Tarcisio Wolff Leal; Leandro Pellenz; Selene Maria de Arruda Guelli Ulson de Souza; Antônio Augusto Ulson de Souza; António Benjamim Mapossa; Robert Kimutai Tewo; Hilary Limo Rutto; Luciano da Silva; Adriano da Silva (Surfaces, 2024)
Society confronts the pressing environmental challenges posed by the pervasive presence of toxic pollutants in aquatic ecosystems. The repercussions of contaminant release extend far and wide, endangering marine life and human well-being. While various techniques such as bioremediation, filtration, and adsorption have been employed for wastewater treatment, they grapple with cost effectiveness and overall efficiency issues. Advanced oxidative processes, including photocatalysis and Fenton, have emerged as viable solutions in response to the emerging contaminants. However, the efficacy of photocatalysis largely hinges on the choice of catalyst. Their distinctive attributes, such as chemical defects and exceptional stability, make perovskite oxides a promising catalyst. These materials can be synthesized through diverse methods, rendering them versatile and adaptable for widespread applications. Ongoing research endeavors are diligently focused on enhancing the performance of perovskite oxides, optimizing their integration into catalytic processes, and exploring innovative approaches for material immobilization. This comprehensive review seeks to elucidate the most pivotal advances in perovskite oxides and their composites within the wastewater treatment domain. Additionally, it sheds light on burgeoning research trends and multifaceted challenges confronting this field, which present insights into techniques for treating the antibiotic-contaminated environment, delving into innovative strategies, green technologies, challenges, and emerging trends.